Trypanosome U-deletional RNA editing involves guide RNA-directed endonuclease cleavage, terminal U exonuclease, and RNA ligase activities. - Cruz-Reyes, J (1996)
We have studied the mechanism of accurate in vitro RNA editing of Trypanosoma brucei ATPase 6 mRNA, using four mRNA-guide RNA (gRNA) pairs that specify deletion of 2, 3, or 4 U residues at editing site 1 and mitochondrial extract. This extract not only catalyzes deletion of the specified number of U residues but also exhibits a novel endonuclease activity that cleaves the input pre-mRNA in a gRNA-directed manner, precisely at the phosphodiester bond predicted in a simple enzymatic model of RNA editing. This cleavage site is inconsistent with a chimera-based editing mechanism. The U residues to be deleted, present at the 3' end of the upstream cleavage product, are then removed evidently by a 3' U-specific exonuclease and not by a reverse reaction of terminal U transferase. RNA ligase can then join the mRNA halves through their newly formed 5' P and 3' OH termini, generating mRNA faithfully edited at the first editing site. This resultant, partially edited mRNA can then undergo accurate, gRNA-directed cleavage at editing site 2, again precisely as predicted by the enzymatic editing model. All of these enzymatic activities cofractionate with the U-deletion activity and may reside in a single complex. The data imply that each round of editing is a four-step process, involving (i) gRNA-directed cleavage of the pre-mRNA at the bond immediately 5' of the region base paired to the gRNA, (ii) U deletion from or U addition to the 3' OH of the upstream mRNA half, (iii) ligation of the mRNA halves, and (iv) formation of additional base pairing between the correctly edited site and the gRNA that directs subsequent nuclease cleavage at the next editing site.